There's a nice proof of the theorem about composite functions (see theorem 5 here) that states

$$(g\circ f)^{-1}=f^{-1}( g^{-1})$$

Notice that $f^{-1}$ means the inverse of $f$. Could anyone help me with proving similar equality for preimages?

The preimage of a function is defined as $f^{-1}[Y]=\{x \in X | f(x) \in Y\}$.

Let $f: X \to Y$ and $g: Y \to Z$. The theorem states that for every subset $S \subseteq Z$:

$$(g\circ f)^{-1}[S]=f^{-1}(g^{-1}[S])$$

So the thing is to show that two sets above are equal.

My attempt would be:

Let $M=(g\circ f)^{-1}[S] = \{x\in X | g(f(x))\in S\}$.

then $g^{-1}[S]$ is a set $G=\{y\in Y | g(y))\in S\}$, and $f^{-1}(g^{-1}[S])=\{x\in X | f(x) \in G\}$.

I'm not sure how to proceed with it next.


1 Answer 1


In general: $$x\in h^{-1}(S)\iff h(x)\in S$$ So the following statements are equivalent:

  • $x\in(g\circ f)^{-1}(S)$
  • $(g\circ f)(x)\in S$
  • $g(f(x))\in S$
  • $f(x)\in g^{-1}(S)$
  • $x\in f^{-1}(g^{-1}(S))$

This shows that $$(g\circ f)^{-1}(S)=f^{-1}(g^{-1}(S))$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.